2015
DOI: 10.2215/cjn.07020714
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Valganciclovir Versus Valacyclovir Prophylaxis for Prevention of Cytomegalovirus in Renal Transplantation

Abstract: Background and objectives Both valganciclovir and high-dose valacyclovir are recommended for cytomegalovirus prophylaxis after renal transplantation. A head-to-head comparison of both regimens is lacking. The objective of the study was to compare valacyclovir prophylaxis with valganciclovir, which constituted the control group.Design, settings, participants, & measurements In a randomized, open-label, single-center trial, recipients of renal transplants (recipient or donor cytomegalovirus-seropositive) were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 40 publications
2
53
4
Order By: Relevance
“…Most of the evidence in this field derives from kidney transplantation. 32,36,37 In a series of studies, Reischig demonstrated that acyclovir prophylaxis is as effective as pre-emptive 36 or prophylaxis 37 with valganciclovir in preventing CMV infection and disease, but with a better safety profile. In addition, acyclovir strategy had a significantly better pharmacoeconomic impact in patient management 37,38 .…”
Section: (Val)acyclovirmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the evidence in this field derives from kidney transplantation. 32,36,37 In a series of studies, Reischig demonstrated that acyclovir prophylaxis is as effective as pre-emptive 36 or prophylaxis 37 with valganciclovir in preventing CMV infection and disease, but with a better safety profile. In addition, acyclovir strategy had a significantly better pharmacoeconomic impact in patient management 37,38 .…”
Section: (Val)acyclovirmentioning
confidence: 99%
“…32,36,37 In a series of studies, Reischig demonstrated that acyclovir prophylaxis is as effective as pre-emptive 36 or prophylaxis 37 with valganciclovir in preventing CMV infection and disease, but with a better safety profile. In addition, acyclovir strategy had a significantly better pharmacoeconomic impact in patient management 37,38 . The drawbacks of acyclovir strategy were an increased rate of biopsy proven rejection when compared to valganciclovir prophylaxis, and a lower long-term graft survival when compared with pre-emptive valganciclovir.…”
Section: (Val)acyclovirmentioning
confidence: 99%
“…In a study analyzing the safety and efficacy of induction treatment with low doses of ATG compared with basiliximab, CMV disease was more frequent in the ATG group despite three months of prophylaxis . In another study, even with valganciclovir (VGCV) prophylaxis, CMV viremia occurred in 8% of patients in another study . Antiviral prophylaxis has been associated with late‐disease (after 3‐6 months) more frequently when compared with preemptive therapy …”
Section: Introductionmentioning
confidence: 99%
“…While the AR‐related costs are not negligible in some European studies, our model may falsely raise the figure in a number of countries with lower hospitalization‐related costs, particularly in the vACV group . Moreover, the difference in the incidence of AR episodes was a result of the increase in less costly mild forms of T cell‐mediated rejection responding well to steroid therapy .…”
Section: Discussionmentioning
confidence: 88%
“…Except for the effect of AR, our economic analysis did not consider the potential long‐term indirect impact of CMV, particularly its effect on graft and patient survival, potentially highlighting the economic benefit of CMV prevention . Still, no differences were found at 1 year between vGCV and vACV prophylaxis in the incidence of CMV disease and DNAemia, renal function, or graft survival . A remarkable finding in this context is that of inferior long‐term graft survival of patients receiving vACV prophylaxis compared with preemptive vGCV therapy .…”
Section: Discussionmentioning
confidence: 98%